2010
DOI: 10.1255/ejms.1050
|View full text |Cite
|
Sign up to set email alerts
|

Current Technological Challenges in Biomarker Discovery and Validation

Abstract: In this review we will give an overview of the issues related to biomarker discovery studies with a focus on liquid chromatography-mass spectrometry (LC-MS) methods. Biomarker discovery is based on a close collaboration between clinicians, analytical scientists and chemometritians/statisticians. It is critical to define the final purpose of a biomarker or biomarker pattern at the onset of the study and to select case and control samples accordingly. This is followed by designing the experiment, starting with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 171 publications
(215 reference statements)
0
19
0
Order By: Relevance
“…For instance, the levels of nitrated proteins in plasma, platelets, and liver tissue were positively correlated with the severity of hepatic cirrhosis [132] and diet-induced obesity [217]. In fact, an excellent review article for identifying potential biomarkers from its discovery to its application in clinical studies has been recently reported [218]. The initial stage is known as the discovery phase with identification of biomarker candidates.…”
Section: Translational Research Using Nitration Proteomics Approacmentioning
confidence: 99%
“…For instance, the levels of nitrated proteins in plasma, platelets, and liver tissue were positively correlated with the severity of hepatic cirrhosis [132] and diet-induced obesity [217]. In fact, an excellent review article for identifying potential biomarkers from its discovery to its application in clinical studies has been recently reported [218]. The initial stage is known as the discovery phase with identification of biomarker candidates.…”
Section: Translational Research Using Nitration Proteomics Approacmentioning
confidence: 99%
“…The course from biomarker discovery to its clinical application can be divided into different stages [28]. The initial stage is known as the discovery phase and reveals biomarker candidates via genomic and proteomic analysis.…”
Section: Proteomic Identification Of Biomarkers and Detection Of Nitrmentioning
confidence: 99%
“…to understand the molecular mechanism of the underlying biological phenomena). This is particularly important in biomarker discovery 69–73 as well as in systems biology 74 studies. Another goal of data processing may be to optimize and assess the performance of LC n ‐MS systems and to compare them to other profiling methods such 1D‐LC‐MS or 2DGE.…”
Section: Processing Of Lcn‐ms Datamentioning
confidence: 99%
“…For that reason, we provide an overview on the most important aspects that such data processing workflow should take into consideration for accurate processing of these types of data. Quantitative data processing workflows for label‐free 1D‐LC‐MS experiments comprise raw data smoothing, peak or feature detection, correction for mass shifts, time alignment and matching of the same peaks or features across multiple chromatograms followed by linking peak identity obtained with peptide sequence identification based on MS/MS spectra to peak quantity 70–72. Methods using stable isotope labelling contain additional modules to extract the relative quantitative peak information from different samples based on defined mass shifts or reporter ion intensities.…”
Section: Processing Of Lcn‐ms Datamentioning
confidence: 99%